INTEGRATED DISTRICT HEALTH CARE SYSTEMS-A REVIEW - Hansotia, Meher F. (Journal of Ayub Medical College Abbottabad, 2000)
Integration has been defined in functional terms as a series of operations concerned in essence with the bringing together of otherwise independent administrative structures, functions and mental attitudes in such a way as to combine these into a whole. However, the expression integrated health services has also been defined in organizational terms as those services necessary for the health protection of people residing in a given area and provided under a single administrative unit, or under several agencies, with proper provision for their coordination.’ Integrated care is an approach whereby health services for a defined population, are financed and delivered through an integrated system, to ensure access, equity and quality of care, in a cost effective way, which is modified by patients, professional and community values.3 A district health system is the vehicle for providing quality primary health care to everyone in a defined geographical area. In this type of health care, individual’s communities and the health providers, participate together in improving their own health. Five important reasons for the introduction of such a system are: